Chemically modified graphene-silver nanocomposites for electrochemical sensor applications / Nurul Izrini Ikhsan - Nurul Izrini , Ikhsan (2018)
Graphene oxide (GO) and reduced graphene oxide (rGO) or known as chemically modified graphene (CMG) are unique building blocks for ‘‘bottom up’’ nanotechnology due to their excellent chemical and physical properties. Composite materials based on CMG and silver nanoparticles (Ag NPs) have been widely studied due to the presence of oxygen functionalities and the assistance of various non-covalent forces. In nanocomposites, CMG serves as a good host material for the accommodation of Ag NPs. In this thesis, four different syntheses were carried out to prepare CMG-Ag nanocomposites and their applicability of serving as an electrochemical sensor material for the detection of important analytes was studied. First, a facile one-pot synthetic method was proposed for the preparation of Ag NPs on GO sheets using garlic extract as a reducing and stabilizing agent and sunlight irradiation as a catalyst. GO sheets provided extra stabilizing for the growth of Ag NPs. As a result, a uniform distribution of Ag NPs on GO sheets with an average size of 19.0 nm was obtained. Second, the time-dependent formation of Ag NPs on rGO sheets was carried out using a modified Tollen’s test. Tollens’ reaction was modified by introducing rGO as a support material for the controlled growth of Ag NPs and the synthesis of rGO-Ag nanocomposite. The reaction was monitored at different time duration (2, 6, 10 and 15 h). With a reaction time of 15 h, almost monodispersed spherical nanoparticles with an average particle size of 16.0 nm were found. Third, the effect of ascorbic acid as a reducing agent for the formation of rGO-Ag nanocomposite was demonstrated. Crystalline and spherical Ag NPs with an average particle size of 2.0 nm were found in the rGO-Ag nanocomposite with the assistance of 5.0 M ascorbic acid. Fourth, the Ag-rGO nanocomposite was in-situ synthesized through a slight modification of Turkevich method using trisodium citrate as a reducing and stabilizing agent. Completely spherical Ag NPs with good distribution and an average particle size of 2.2 nm was found using 4 mM AgNO3. In the following part, the modified electrodes of CMG-Ag nanocomposites obtained using various methods were applied as sensor electrodes for the electrochemical detection of various analytes. The proposed sensors displayed good sensitivity and selectivity towards target molecules such as nitrite ions, 4-nitrophenol (4-NP), nitric oxide (NO) and hydrogen peroxide (H2O2). In addition to the interesting detection limits, the nanocomposite modified electrodes showed acceptable reproducibility, repeatability, and stability during the sensing experiments. Lastly, the applicability of the present nanocomposites was demonstrated in real water samples. The observed good recoveries implied that the present electrochemical sensors could be used for the detection of nitrite ions, 4-NP, NO and H2O2 in environmental water samples.